A informação na ciência da informação: mapeamento do conceito de informação em alguns periódicos brasileiros - Santos, Raiane da Silva [UNESP] (Unigoiás, 2021)
This study aims to analyze the information concepts used in the main journals in the area of Information Science through the analysis of articles published in the journals Perspectives in Information Science (PCI) and Information & Society: studies (I&S), in the years from 2019 and 2020. The exploratory descriptive type, of a qualitative and quantitative nature, uses documentary reading as a data collection technique. 153 articles were selected, of which 80 presented the term information in the title and / or keywords field. Of these, 11 conceptualized information in their texts. It was concluded that the term information is a subject widely addressed in the articles, however, its conceptualization is little discussed. It was also found that Buckland and Le Coadic are the authors most cited in the researched journals, however, there is no defined theoretical framework for research on the topic, since there was a large dispersion of authors in the evaluated articles.

Este estudo tem por objetivo analisar os conceitos de informação utilizados nos principais periódicos da área de Ciência da Informação através da análise dos artigos veiculados nos periódicos Perspectivas em Ciência da Informação (PCI) e Informação & Sociedade: estudos (I&S), nos anos de 2019 e 2020. Do tipo exploratório descritiva, de natureza quali-quantitativa, utiliza da leitura documental como técnica de coleta de dados. Foram selecionados 153 artigos, dos quais 80 apresentavam o termo informação no campo de título e/ou palavras-chave. Destes, 11 conceituaram a informação em seus textos. Concluiu-se que o termo informação é um assunto bastante tratado nos artigos, porém, sua conceituação é pouco discutida. Constatou-se também que Buckland e Le Coadic são os autores mais citados nos periódicos pesquisados, contudo, não há um referencial teórico definido para as pesquisas no tema, uma vez que se verificou uma grande dispersão de autores nos artigos avaliados.
Keywords: Concept of information; Information science; Concept mapping; Conceito de informação; Ciência da informação; Mapeamento de conceito